Edukasi Teologis tentang Pernikahan Dini dalam Gereja - Marta Regina; Martina Novalina (THRONOS: Jurnal Teologi Kristen, 2022)
RI Law Number 16 of 2019 Article 7 paragraph 1 explains that marriage is allowed if the male and female parties have reached the age of 19 years. If the marriage is carried out below the minimum age stated in the law, then the marriage is classified as early marriage. There are so many problems that can arise due to early marriage, such as reproductive health problems, psychological problems and even early marriage can affect self-concept in adolescents. In developing this paper, the author uses qualitative research methods with a literature study approach to further review the phenomenon of early marriage in adolescents. That way, the church as a representation of God has responsibility for the reality that is happening. The church, especially the youth pastor, must make young people aware of the importance of finding a life partner according to God's will. As believers, Christian youth not only have to struggle with their soulmate before God but also have to struggle with whether God wants them to get married or not. Because the principle of truly Christian life is to marry for the glory of God.  AbstrakUU RI Nomor 16 Tahun 2019 pasal 7 ayat 1 menerangkan bahwa perkawinan diperkenankan jika pihak laki-laki dan perempuan sudah menginjak usia 19 tahun. Jika perkawinan dilakukan di bawah usia minimum yang tertera pada hukum, maka perkawinan tersebut tergolong ke dalam perkawinan dini. Terdapat begitu banyak masalah yang dapat timbul akibat perkawinan dini, seperti: masalah kesehatan reproduksi, masalah psikologis, bahkan perkawinan dini dapat memengaruhi konsep diri pada remaja. Dalam mengembangkan tulisan ini, penulis menggunakan metode penelitian kualitatif dengan pendekatan studi kepustakaan untuk meninjau lebih jauh fenomena perkawinan dini pada remaja. Dengan begitu, gereja sebagai representasi Tuhan memiliki tanggung jawab terhadap realitas yang terjadi. Gereja, terkhusus pembina remaja, harus menyadarkan para remaja akan pentingnya menemukan pasangan hidup sesuai kehendak Tuhan. Sebagai orang percaya, remaja Kristen bukan saja harus menggumuli jodohnya di hadapan Tuhan, tetapi harus menggumuli apakah Tuhan menghendakinya untuk menikah atau tidak. Sebab, prinsip hidup orang Kristen yang benar adalah menikah untuk meninggikan Tuhan.